Pink eye outbreak in rural Borneo schools : The panic and the prompt public health response - Sam Froze, Jiee; Aina S., Aziz; Lim, Siong Hee; Muhamad A., Qamil; Jeffery, Stephen (Wolters Kluwer – Medknow, 2025)
BACKGROUND: On September 28, 2022, a rural health clinic reported unusual eye symptoms in students from five schools in Sri Aman Sarawak, a rural region of Borneo. The objective of our investigation was to verify the diagnosis, identify the source of infection, conduct active case findings, and implement control and preventive measures. MATERIALS AND METHODS: Our case definition included eye redness, discharge, or watering in students, staff, or their family members in Sri Aman since early September 2022. Descriptive epidemiology included active case finding and the construction of an epidemic curve. A retrospective cohort study was conducted to investigate the outbreak of conjunctivitis in students and staff in specific schools, allowing for the identification of exposed individuals and calculation of accurate attack rates. RESULTS: We identified 228 cases of acute conjunctivitis in three boarding schools and four day schools, with an incubation period ranging from 24 to 78 hours. Most of the cases were secondary school students, comprising 56.6% of the total, with a nearly equal gender distribution of 51.3% male and 48.7% female. Bilateral involvement was observed in 61.8% of the cases. The overall attack rate was 8.5%. CONCLUSION: Good personal hygiene, prompt isolation of unwell students, and efficient event‑based surveillance systems in healthcare facilities are crucial for the prevention of the spread of infectious diseases in schools and the protection of public health through early detection and intervention.